Peru : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2003)
The coverage, periodicity, and timeliness for macroeconomic data in Peru are summarized and compared with Special Data Dissemination Standard (SDDS) specifications. The human, financial, and computing resources allocated to the existing program of statistics at the Central Reserve Bank of Peru (CRBP) are adequate and are used efficiently. The CRBP has well-established recruitment and training programs, and the salaries are competitive compared with those of the private sector. Efforts are being made to upgrade the computer systems, including the recent acquisition and implementation of new software to manage the macroeconomic databases.